Implementasi Program Pelatihan “Perhutani Start Program” dalam Upaya Peningkatan Kinerja Sumber Daya Manusia Di Perhutani Forestry Institute Madiun - Rachma Khaerani, Dwi; Ichsanuddin Nur, Dhani (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
Community service activity aimed at improving human resource performance at Perum Perhutani. The primary focus of this activity is strengthening employee character, leadership, and professionalism as key factors in supporting sustainable organizational performance. Developing these aspects is considered crucial given the increasingly dynamic and competitive demands of organizations. The activity was implemented through two main methods: socialization and discussion. The socialization method was used to systematically deliver material related to character development, leadership, and professionalism, while the discussion method was used to encourage active participant participation, share experiences, and deepen understanding of the material presented. This combination of these two methods was designed to ensure a non- unidirectional learning process and foster reflective awareness among participants. The results of the activity demonstrated a positive response from the participants. This was evident in the high level of enthusiasm throughout the activity and the increased awareness of the importance of developing personal competencies to support work performance. The implementation of the socialization and discussion methods has proven effective in supporting the sustainable improvement of human resource performance. This program has had a positive impact on human resource development at Perum Perhutani and has the potential to be implemented as a routine development program in the future.